2023
DOI: 10.1158/1078-0432.ccr-23-1349
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Clinical Trial of Pembrolizumab and Chemotherapy Reveals Distinct Transcriptomic Profiles by Radiologic Response in Metastatic Triple-Negative Breast Cancer

Avia D. Wilkerson,
Prerana Bangalore Parthasarathy,
Nickolas Stabellini
et al.

Abstract: Purpose A single arm, Phase II trial of carboplatin, nab-paclitaxel, and pembrolizumab (CNP) in metastatic triple negative breast cancer (mTNBC) was designed to evaluate overall response rate (ORR), progression-free survival (PFS), duration of response (DOR), safety/tolerability, overall survival (OS), and identify pathologic and transcriptomic correlates of response to therapy. Patients/Methods Patients with ≤2 prior therapies for metastatic disease were treated with CNP regardless of tumor PD-L1 status. Core… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Increased immune activity in the tumor before treatment is correlated with the efficacy of nab-paclitaxel and pegylated liposomal doxorubicin when combined with anti-PD-1/PD-L1 therapy ( Table 1 ). A clinical study that combined nab-paclitaxel with pembrolizumab showed that a complete response was correlated with increased immune activity in the pre-treated tumor through a gene set enrichment analysis ( 20 ). Another study that combined nab-paclitaxel with atezolizumab showed that tumor infiltrating lymphocytes were associated with PD-L1 positive tumors, both of which were correlated with progression-free survival and overall survival ( 21 ).…”
Section: Clinical Studies Of Nanoparticle Formulation-pd-1/pd-l1 Inhi...mentioning
confidence: 99%
“…Increased immune activity in the tumor before treatment is correlated with the efficacy of nab-paclitaxel and pegylated liposomal doxorubicin when combined with anti-PD-1/PD-L1 therapy ( Table 1 ). A clinical study that combined nab-paclitaxel with pembrolizumab showed that a complete response was correlated with increased immune activity in the pre-treated tumor through a gene set enrichment analysis ( 20 ). Another study that combined nab-paclitaxel with atezolizumab showed that tumor infiltrating lymphocytes were associated with PD-L1 positive tumors, both of which were correlated with progression-free survival and overall survival ( 21 ).…”
Section: Clinical Studies Of Nanoparticle Formulation-pd-1/pd-l1 Inhi...mentioning
confidence: 99%